Economic Problems of Kazakhstan's Competitiveness in the International Tourist Business - BATYROVA, Nazygul; YERMANKULOVA, Rima; MOMBEKOVA, Gulmira; JAXILIKOV, Almas (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).04, 2018)
The paper analyzes the current system of strategic business development in the sphere of tourism and determines the possibility for the functioning of strategic planning of the economic sphere of tourism in Kazakhstan. The relevance of the work is determined in the need to change the structure of the attractiveness of the tourism industry in the aspect of increasing the regional advantages of the country to participate in the globalized tourist flow. The authors determine that the share of tourism in the GDP of Kazakhstan is determined at the level of countries that are generally represented in tourism, but there is no significant growth and a significant share in GDP. It is determined that each of the components of tourism can bring additional income, which will be comparable with the share of the service and industrial industries of the state. The authors understand the novelty of the study by the fact that tourism is in fact not only an economic, but also a socio-political category. The article notes that the results of mathematical modeling confirm the possibility of using a social tool for the design of strategic forms of development of the tourism industry. Directions of further research authors suggest to consider a place of tourism in the economy of Kazakhstan taking into account the internal programs of stimulation of tourist activity at the international level in various integration associations. This includes both Kazakhstan's participation in the current economic unions and its gradual development of its participation in international tourism exchanges.